Gut microbiota, inflammatory bowel disease and colorectal cancer - Quaglio, Ana Elisa Valencise [UNESP]; Grillo, Thais Gagno [UNESP]; De Oliveira, Ellen Cristina Souza [UNESP]; Di Stasi, Luiz Claudio [UNESP]; Sassaki, Ligia Yukie [UNESP] (Baishideng Publishing Group, 2022)
The gut microbiota is a complex community of microorganisms that inhabit the digestive tracts of humans, living in symbiosis with the host. Dysbiosis, characterized by an imbalance between the beneficial and opportunistic gut microbiota, is associated with several gastrointestinal disorders, such as irritable bowel syndrome (IBS); inflammatory bowel disease (IBD), represented by ulcerative colitis and Crohn’s disease; and colorectal cancer (CRC). Dysbiosis can disrupt the mucosal barrier, resulting in perpetuation of inflammation and carcinogenesis. The increase in some specific groups of harmful bacteria, such as Escherichia coli (E. coli) and enterotoxigenic Bacteroides fragilis (ETBF), has been associated with chronic tissue inflammation and the release of pro-inflammatory and carcinogenic mediators, increasing the chance of developing CRC, following the inflammation-dysplasia-cancer sequence in IBD patients. Therefore, the aim of the present review was to analyze the correlation between changes in the gut microbiota and the development and maintenance of IBD, CRC, and IBD-associated CRC. Patients with IBD and CRC have shown reduced bacterial diversity and abundance compared to healthy individuals, with enrichment of Firmicute sand Bacteroidetes. Specific bacteria are also associated with the onset and progression of CRC, such as Fusobacterium nucleatum, E. coli, Enterococcus faecalis, Streptococcus gallolyticus, and ETBF. Future research can evaluate the advantages of modulating the gut microbiota as preventive measures in CRC high-risk patients, directly affecting the prognosis of the disease and the quality of life of patients.
Keywords: Colorectal cancer; Crohn’s disease; Dysbiosis; Gut microbiota; Inflammatory bowel disease; Ulcerative colitis